In Situ Generated Sulfate-Facilitated Efficient Nitrate Electrosynthesis on 2D PdS2 with Unique Imitating Growth Feature - Zhang, Rui; Mao, Hui; Wang, Ziyi; Ma, Shengke; Wu, Shuyao; Wu, Qiong; Liu, Daliang; Li, Hui; Fu, Yang; Li, Xiaoning; Ma, Tianyi (Nano-Micro Letters, 2025)
As a green sustainable alternative technology, synthesizing nitrate by electrocatalytic nitrogen oxidation reaction (NOR) can replace the traditional energy-intensive Ostwald process. But low nitrogen fixation yields and poor selectivity due to the high bond energy of the N≡N bond and competition from the oxygen evolution reaction in the electrolyte restrict its application. On the other hand, two-dimensional (2D) PdS2 as a member in the family of group-10 novel transition metal dichalcogenides (NTMDs) presents the interesting optical and electronic properties due to its novel folded pentagonal structure, but few researches involve to its fabrication and application. Herein, unique imitating growth feature for PdS2 on different 2D substrates has been firstly discovered for constructing 2D/2D heterostructures by interface engineering. Due to the different exposed chemical groups on the substrates, PdS2 grows as the imitation to the morphologies of the substrates and presents different thickness, size, shape and the degree of oxidation, resulting in the significant difference in the NOR activity and stability of the obtained composite catalysts. Especially, the thin and small PdS2 nanoplates with more defects can be obtained by decorating poly(1-vinyl-3-ethylimidazolium bromide) on the 2D substrate, easily oxidized during the preparation process, resulting in the in situ generation of SO42−, which plays a crucial role in reducing the activation energy of the NOR process, leading to improved efficiency for nitrate production, verified by theoretical calculation. This research provides valuable insights for the development of novel electrocatalysts based on NTMDs for NOR and highlights the importance of interface engineering in enhancing catalytic performance. Highlights: 1 Unique imitating growth feature for PdS2 on different 2D substrates has been firstly discovered for constructing 2D/2D heterostructures by interface engineering. 2 The thin and small PdS2 nanoplates with active defects can be inducted by poly(1-vinyl-3-ethylimidazolium bromide (PVEIB), resulting in the obtained PdS2@PVEIB/PPy/GO exhibited the excellent nitrogen oxidation reaction (NOR) electroactivity with the outstanding stability and selectivity. 3 The in situ generation of SO42−, caused by the oxidation during the preparation process or exposed in air, as well as at high NOR potential, plays a crucial role in reducing the activation energy of the NOR process, leading to improved efficiency for nitrate production.